Validation of the names of eight species of Blattaria according to the Rules of Zoological Nomenclature - Lopes, Sonia Maria; de Oliveira, Edivar Heeren (Zootaxa, 2018)
According to information provided by Krell & Pape (2015), in articles 8, 9, 10, 21 and 78 of the International Code of Zoological Nomenclature (ICZN 1999) after the 2012 Amendment (ICZN 2012a, b, c), the publication methods are expanded and improved. One of the requirements for electronic publication to be available for Nomenclatural Actions is that publications have to be registered in the Official Register of Zoological Nomenclature (ZooBank.org), by enabling the work to be potentially compatible with the code in its final version, in which the correct date of publication must be provided, guaranteeing the nomenclatural priority of the electronic version. Failure to follow these measures will keep the information recorded from being known to the scientific community.